I, robot - Asimov, Isaac (London : Harper Voyager, 2013)
Nine science fiction stories about robots, including "Runaround," "Little Lost Rabbit," "Evidence," "Reason," and "The Evitable Conflict.".
5.6
Young Adult.
Young Adult
Keywords: Robots -- Fiction; Science fiction; Short stories; Robots -- Fiction; Science fiction; Short stories